Numerical treatment and experimental tests of phenol removal in batch and fixed bed column using activated carbon Tratamento numérico e ensaios experimentais da remoção de fenol em reator batelada e coluna de leito fixo utilizando carvão ativado - Meneghini A. (2021)
© 2021 Associação Brasileira de Engenharia Sanitária e Ambiental.In this study, the kinetics and adsorption isotherms of phenol present in synthetic effluents were obtained in a batch reactor and fixed bed column, using adsorbent coconut shell activated carbon. The objective was to obtain the kinetic and equilibrium parameters of the process to simulate different operating conditions in a fixed bed adsorption column. The influence of the pH, adsorbent mass, initial phenol concentration, and three different temperatures for the batch reactor tests were evaluated. It was possible to work on the natural pH of the solution and the temperature increase indicated exothermic, favorable, and spontaneous adsorption. Both isotherm models (Langmuir and Freundlich) represented the experimental data (R2 ≈ 0.9). Approximate values of maximum adsorption capacity were found for the batch reactor and for the fixed bed column (qmax = 41.69 mg g-1 for the batch reactor and qmax = 41.98 mg g-1 for the fixed bed column). The Finite Volume method was used in the discretization of the mathematical equations and a computational algorithm was implemented in FORTRAN programming language. The computational code was validated with experimental data of this work (mean error of 13%) and it was possible to simulate different operational conditions of the fixed bed column adsorption system for future industrial applications.